Zeotropic mixture active design method for organic Rankine cycle. (25th January 2018) - Zhai, Huixing; An, Qingsong; Shi, Lin
Highlights: A zeotropic mixture active design method is provided for organic Rankine cycle. The designed mixtures have better performance than the optimal pure working fluid. Mixtures can increase the heat source utilization rate. Using this active design method can avoid massive calculation for mixture selection. Abstract: Using mixture working fluids has been proven to be an effective way to improve the performance of organic Rankine cycles (ORC). Instead of recommending mixtures or compositions for a specific heat source, this work is focused on providing preliminary design guidelines of zeotropic mixture working fluids for ORC. The zeotropic mixture active design method is provided for mixture selection without massive calculation or blind trial. The designed mixtures have better performance than the optimal pure working fluid. The designed zeotropic mixtures should have the same key properties as the optimal pure working fluids and also have temperature glide matching with the cooling source. Firstly, the authors' previous study on the optimal pure working fluid screen criteria is simply reviewed. Then, how the mixture's temperature glide influencing on the cycle performance is analyzed. Finally, the zeotropic mixture active design method is provided and verified. Some debatable questions regarding to the mixtures are also answered.